"A reward rather than a right": Facilitators' perspectives on the place of music in Norwegian prison exceptionalism. (September 2021) - Mangaoang, Áine
Scholarship on prison music-making projects and programmes to date has largely overlooked the perspectives of prison music facilitators, who form an integral part of many prison music activities. The aim of the study, which was exploratory in nature, was to contribute to a better understanding overall of the relationship between music and imprisonment by focusing on the perspectives of prison music practitioners. Drawing from data collected in four Norwegian prisons through ethnographic research, data was analysed thematically with four key themes emerging: interpersonal communication and emotional connection; social responsibility; prison system and environment, and (in)difference and exclusion. The findings highlight the fact that the range of prison music activities offered in many Norwegian prisons affects music facilitators deeply in a number of ways, and support existing studies that find that prison music practices can contribute to creating a community of caring individuals both inside and outside prisons. Notably, the emergence of the (in)difference and exclusion theme demonstrates a more critical and nuanced view of prison music facilitators' experiences as going beyond simplistic, romantic notions of music's function in social transformation. Concerns raised for those who appear to be excluded or differentiated from music-making opportunities in prison – in particular foreign nationals and women – suggest that (even) in the Norwegian context, music in prisons remains a "reward" rather than a fundamental "right." This study marks a step towards a richer and more critical understanding of prison musicking and aims to inform future research, practice, and the processes involved in the possibilities for offering music in prisons.